Quantifying the diagenetic impact in the late Ediacaran and early Palaeozoic of the Avalon Peninsula using illite “crystallinity” - Austermann, Gregor; Kling, Melanie; Ifrim, Christina; Emondt, Pascale D.; Hildenbrand, Anne (Canadian journal of earth sciences, 2021)
The Avalon Peninsula on the island of Newfoundland, Canada, defined as the type zone of Avalonia, is believed to have been impacted by several orogenetic and deformation events since the Neoproterozoic. Previous studies have determined that the lowest degree of metamorphism reached in the successions was of the prehnite–pumpellyite or greenschist facies. We sampled and measured 13 mainly clastic sedimentary sections ranging from the late Ediacaran to the Early Ordovician and analyzed the illite “crystallinity” of 331 samples using the Kübler index. Our results show that the occurrence of diagenetic zones relates to lithology, age and burial depth, and regional setting. Samples adjacent to the fault zones bounding the Holyrood Horst experienced the highest degree of metamorphism (anchizone) in the study area. The lowest degree of thermal alteration occurs in the high stratigraphic sections at the centre of the horst structure where shallow diagenetic conditions are preserved. Fault zones, which were probably active during at least the Acadian Orogeny, may have served as potential paths for hot fluids in bounding areas of the horst, whereas the centre of the horst remained almost unaffected by any metamorphic overprint. The thermal impact decreases from the Bonavista Peninsula west of the study area from greenschist facies to anchizonal and diagenetic. The study area experienced lower metamorphic conditions than those in the major regions of Avalonia south of the study area, namely the mainland of New Brunswick and Maine and eastward in Europe, but is in part consistent with a few other areas of Avalonia, such as the Mira Terrane and the Antigonish Highlands in Nova Scotia.
Gesehen am 01.12.2021